Female Voices Undermining Male Voices in Protests, 2023 (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
In this article we examined the phenomenon of women in leadership positions in the civil protest over the 2023 judicial reform protests. We focused on how women interpret social change, advance it, and act as its agents while facing tensions and gender-related obstructions in civil spaces. Using a qualitative study based on interviews with female founders and leaders of protest organizations, we chose the factors that influenced the establishment of female leaders within the protest. In our analysis, we relied on theoretic approaches that combine the Politics of Presence with Ambivalent Sexism Theory alongside terms of agency. We uncovered three central themes: the first – Politics of Presence and Representation – showed how female leaders used personality and gender characteristics to demand a place and authority while suggesting an alternative and varied leadership model that relied on their intersectional identity. The second theme – the inter-liberal struggle – exemplified their twofold fight against the government and the patriarchal patterns within the liberal camp itself. The third theme – hostile and benevolent sexism – depicted how they dealt with attempts at delegitimization whilst using their identity as a strategic resource. The main conclusion is that the assertive presence of these women was used as an agent of change that undermined patriarchal discourse both in the public and interior liberal arenas, thus promoting gender equality and a broader social political transformation. The study’s main contribution is in its presentation of female leaders as active agents whose varied voices do not reflect a unified essence as women but rather deconstruct existing power structures and broaden the boundaries of protest.
Keywords: Protest; Female Leadership; Ambivalent Sexism; Politics of Presence; Agency